Toxicological effects of a herbicide – Pendinmethalin: a case study of Kenana Sugar Industry, White Nile Province, Sudan - Abdelgadir, Muawia IA; Sabahelkhier, Murwan K; Adris, Mohamed A; Idris, Omer F; Adam, Shama IY; Sulafa, HN (International Journal of Environment, 2014)
The aim of this experiment is to know the toxicity of high uses of pendimethalin as herbicide used in Kenana Sugar Industry, period of experiment is 30 days. The results were reveal that there was significantly effect of high doses of pendimethalin on the liver of Wistar rats, because increase in the dose of the pendimethalin reflected by increasing the alkaline phosphatase enzyme during increase the period of time. In addition there were histopathological medical in cells of the liver of Wistar rats, which lead to impaired function of the liver, so it is very clear observed in water collected from Kenana Sugar Industry plate two, and 375 and 750 (plate three and four) compared with plate one( free from pendimethalin treatment. This experiment indicated that high dose of pendimethalin causes toxicity. DOI: http://dx.doi.org/10.3126/ije.v3i2.10638 International Journal of the Environment Vol.3(2) 2014: 258-262